Experiencing Public dan Evaluating Public: Dinamika Pembentukan Citra Hotel Keluarga pada Program Cooking Class di Lynn Hotel Mojokerto - Inggrid Putri Ariyanto; Masnia Ningsih; Rakhmad Saiful Ramadhani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The competitive hotel industry requires hotels to build an image that differentiates them from competitors, including an image as a family hotel. This study aims to analyze how a family-hotel image is formed when the public that experiences a program and the public that evaluates it are different parties, using the children's cooking class program at Lynn Hotel Mojokerto as a case. A qualitative descriptive approach was employed; data were collected through observation, in-depth interviews with seven purposively selected informants (hotel management, event organizer, school, and parents), and documentation, then analyzed using the Miles and Huberman model with source and technique triangulation. The findings show that the family-hotel image is formed through Jefkins' four stages of image formation, yet with a distinctive characteristic, namely a split in public roles: children act as the experiencing public, whereas parents act as the evaluating public who ultimately form and retain the image. The two are connected through direct observation and emotional re-narration, and direct experience proves to be a more effective channel for introducing the hotel than formal promotion. This study enriches image theory for family-based services and recommends managing programs that satisfy both publics simultaneously.